Late Quaternary Biomass Burning in Northwest Africa and Interactions With Climate, Vegetation, and Humans. Issue 2 (1st February 2019) - Schreuder, Laura T.; Hopmans, Ellen C.; Castañeda, Isla S.; Schefuß, Enno; Mulitza, Stefan; Sinninghe Damsté, Jaap S.; Schouten, Stefan
Abstract: Biomass burning on the African continent is widespread, and interactions with climate, vegetation dynamics, and biogeochemical cycling are complex. To obtain a better understanding of these complex relationships, African fire history has been widely studied, although mostly on relatively short timescales (i.e., years to kiloyears) and less commonly on long‐term scales. Here we present a 192‐kyr, continuous biomass‐burning record from sub‐Saharan Northwest Africa based on the fire biomarker levoglucosan in a marine sediment core offshore Guinea. Notable features of our record include an increase in levoglucosan accumulation at 80 ka and two peaks at 50–60 ka. The event at 80 ka is likely related to an overall increase in sedimentation rates rather than an increase in biomass burning in the Northwest African savanna region. Our record indicates that glacial/interglacial changes in regional climate and vegetation composition (C3 vs. C4 plants) were not a major influence on biomass burning over the last 192 kyr. However, we suggest that the burning events at 50–60 ka might be caused by increased occurrence of C3 vegetation and human settlement in this region. At this time, the savanna region became wetter and fuel loads likely increased. Therefore, the region was more hospitable for humans, who likely used fire for hunting activities. Collectively, we hypothesize that on longer (glacial/interglacial) timescales, biomass burning, regional climate, and African vegetation are not necessarily coupled, while around 50–60 ka, higher fuel loads and human fire use may have influenced fire occurrence in sub‐Saharan Northwest Africa. Key Points: Biomass burning history of sub‐Saharan Northwest Africa during the last 192 kyr was studied, based on levoglucosan accumulation rates Glacial/interglacial changes in regional climate and vegetation composition were not a major influence on biomass burning Fire events around 50–60 ka in sub‐Saharan Northwest Africa might be caused by increased fuel loads and human fire use